ChemInform Abstract: Amination of ω‐Functionalized Aliphatic Primary Alcohols by a Biocatalytic Oxidation—Transamination Cascade. Issue 7 (January 2016) - Pickl, Mathias; Fuchs, Michael; Glueck, Silvia M.; Faber, Kurt
Abstract: A five‐enzyme cascade for the amination of primary alcohols by coupling a long‐chain alcohol oxidase with an ω‐transaminase is successfully extended to also encompass nonactivated fatty alcohols as substrates.